Nutritional Status and Factors Affecting Nutrition Among Adolescent Girls in Urban Slums of Dibrugarh, Assam - Bhattacharyya, Himashree; Barua, Alak (National Journal of Community Medicine, 2013)
Objective: To assess the nutritional status and and factors affecting nutrition of adolescent girls residing in urban slums of Dibrugarh town. Methods-A community based cross sectional study of 284 adolescent females in the age group 10-19 years was conducted in all the 10 slums in Dibrugarh town . The BMI for age <5th percentile and height for age< 3rd percentile or <-2 Z scoresof NCHS reference standard were used as criteria for thinness and stunting respectively. Results: The overall prevalence of thinness was 25.70% and the prevalence of stunting was 31.33%. A significant association was observed between the nutritional status of adolescents and the mother’s literacy level and family size. The various morbidities prevalent amongst the adolescent girls were found to be pallor (93.30%); menstrual problems (83.09%); dentalcaries (42.25%); angular stomatitis (35.56%); glossitis (34.15%); Skin problems (20.07 %); lymphadenopathy (10.21%) diarrhoea (7.04%), Goitre (4.22%) and bitots spots (0.35%).